2021
DOI: 10.3389/fmicb.2021.669937
|View full text |Cite
|
Sign up to set email alerts
|

Candidatus Methylumidiphilus Drives Peaks in Methanotrophic Relative Abundance in Stratified Lakes and Ponds Across Northern Landscapes

Abstract: Boreal lakes and ponds produce two-thirds of the total natural methane emissions above the latitude of 50° North. These lake emissions are regulated by methanotrophs which can oxidize up to 99% of the methane produced in the sediments and the water column. Despite their importance, the diversity and distribution of the methanotrophs in lakes are still poorly understood. Here, we used shotgun metagenomic data to explore the diversity and distribution of methanotrophs in 40 oxygen-stratified water bodies in bore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 106 publications
(183 reference statements)
2
7
0
Order By: Relevance
“…Frontiers in Environmental Science frontiersin.org lake were elevated throughout the water column (2 μM-27 μM), consistent with the ubiquitous presence of type I methanotrophs, which have been suggested to have lower methane affinity compared to type II methanotrophs (Martin et al, 2021).…”
Section: Figuresupporting
confidence: 64%
See 1 more Smart Citation
“…Frontiers in Environmental Science frontiersin.org lake were elevated throughout the water column (2 μM-27 μM), consistent with the ubiquitous presence of type I methanotrophs, which have been suggested to have lower methane affinity compared to type II methanotrophs (Martin et al, 2021).…”
Section: Figuresupporting
confidence: 64%
“…Methylumidiphilus within the order Methylococcales, had high relative abundances throughout the lake, but Alphaproteobacteria known to be type II methanotrophs had high relative abundance in surface water where methane concentrations were comparatively low (0 μM-1 μM) (Martin et al, 2021). In comparison, methane concentrations in Teardrop (A-C).…”
Section: Figurementioning
confidence: 97%
“…Strain S3L5C, isolated and classified in this study as Methylobacter sp., has been previously reported to be a dominant genus in the oxic-anoxic transition zone in boreal and subarctic lakes, ponds, and wetlands [ 7 , 8 , 10 , 11 , 50 52 ]. Our phylogenetic and phylogenomic tree analyses showed that the isolate represents a ubiquitous cluster of Methylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Strain S3L5C, isolated and classified in this study as Methylobacter sp., has been previously reported to be a dominant genus at oxic-anoxic transition zone in boreal and subarctic lakes, ponds and wetlands (Cabrol et al, 2020; Cassarini et al, 2019; Martin et al, 2021; Rissanen et al, 2021b, 2018; Smith et al, 2018; van Grinsven et al, 2021a). Our phylogenetic and phylogenomic tree analyses showed that the isolate represents a ubiquitous cluster of Methylobacter spp.…”
Section: Discussionmentioning
confidence: 98%